REDD+ benefit sharing in Ethiopia: policy and stakeholder perceptions analysis - Pham Thu Thuy; Moeliono, M.; Dwisatrio, B.; Yuwono, J.; Atmadja, Stibniati (Commonwealth Forestry Association, 2021)
Current Ethiopian policies and laws recognize the importance of equitable benefit-sharing mechanisms for natural resource management. The question of ‘what is fair’ is often unclear in practice. We pursue this question in the context of benefit sharing for Reducing Emissions from Deforestation and Forest Degradation (REDD+) in Ethiopia. We present findings from interviews conducted in 2017 with 33 national REDD+ actors, and a review of national policies and laws until 2020 to understand Ethiopia’s policy and legal framework, and vision for a REDD+ benefit-sharing mechanism. Our findings show that Ethiopia is progressing in developing a benefit-sharing mechanism (BSM) for REDD+. Government policies on benefit sharing are pro-poor with an emphasis on legal rights. Among the various concepts of fairness, more stakeholders agreed that benefits should be shared according to efforts made to reduce deforestation and forest degradation rather than being based on poverty or legal rights. Left unattended, we believe this divergence of opinion on ‘what is fair’ opens the potential for questions regarding the legitimacy of the REDD+ BSM among stakeholders in general and can pose practical implementation challenges. We suggest that establishing open dialogue, learning mechanisms and inclusive processes can lead to regulations, policies and procedures that clarify and harmonize the different views on fairness over time.